2013
DOI: 10.1364/ol.38.003592
|View full text |Cite
|
Sign up to set email alerts
|

Two techniques for temporal pulse compression in gas-filled hollow-core kagomé photonic crystal fiber

Abstract: We demonstrate temporal pulse compression in gas-filled kagomé hollow-core photonic crystal fiber (PCF) using two different approaches: fiber-mirror compression based on self-phase modulation under normal dispersion, and soliton effect self-compression under anomalous dispersion with a decreasing pressure gradient. In the first, efficient compression to near-transform-limited pulses from 103 to 10.6 fs was achieved at output energies of 10.3 μJ. In the second, compression from 24 to 6.8 fs was achieved at outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…This new type of PCF offers a relatively large core (30-60 mm), low propagation loss and allows studying a variety of nonlinear effects 37 . Interestingly, the Kagome PCF has been recognized as the perfect waveguide for nonlinear compression of mJ-level pulses 38,39 , whereas conventional capillaries have extremely high propagation losses due to the required small diameter. Furthermore, they can be operated at high average powers 40 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This new type of PCF offers a relatively large core (30-60 mm), low propagation loss and allows studying a variety of nonlinear effects 37 . Interestingly, the Kagome PCF has been recognized as the perfect waveguide for nonlinear compression of mJ-level pulses 38,39 , whereas conventional capillaries have extremely high propagation losses due to the required small diameter. Furthermore, they can be operated at high average powers 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Further spectral broadening was not possible with this specific fiber due to the occurrence of other nonlinear effects. However, it has already been demonstrated that proper fiber designs allow for the achievement of 10 fs pulses 39 . Temporal compression is then achieved using four reflections on highly dispersive and broadband (2350 fs 2 per reflection, 980-1080 nm) chirped mirrors.…”
Section: Methodsmentioning
confidence: 99%
“…The stateof-the-art approach to generate these pulses uses frequency conversion and amplification via OPA. High-energy pump and seed for OPA eventually relies on CPA schemes followed by nonlinear spectral broadening [15,16]. However, access to the long MIR wavelengths has been limited due to the nearly exclusive use of near-infrared (NIR) pump sources at 800 nm and 1 μm [17].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the pulse-compression experiments demonstrated so far in Kagome fibers have used input pulses of sub-ps duration [15,[35][36][37]. Consequently, due to the high peak power, the throughput pulse energy of those experiments was limited to few hundreds of micro-joule energy in the presence of air [30].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1(a) shows the experimental spectra at the fiber output. The following phenomena can be identified: soliton self-compression [12,13] (for input energies smaller than 4 μJ), supercontinuum generation [15], DW emission [16,17] and soliton blue-shifting [8] (between 4 and 8 μJ), and finally a novel effect: plasmainduced soliton fission for input energies greater than 8 μJ. These effects will be explained in the following, and the origin of the plasma-induced soliton fission identified.…”
mentioning
confidence: 99%